Rare case of broad ligament fibroid with cystic degeneration - Hada, Anupama; Sen, Sangeeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Giant fibroids are known to arise from the uterus, although very rarely from extra-uterine sites. Among extra-uterine fibroids, broad ligament fibroids generally achieve enormous size and generally present with pressure symptom like bladder and bowel dysfunction. Cystic degeneration is a rare complication of benign fibroid, where presence of cystic changes mimics the ovarian tumor. We report a case of false broad ligament fibroid. This case is reported for its rarity and the diagnostic difficulties in differentiating ovarian tumor and benign fibroid with cystic degeneration.